Financial dollarization and European Union membership - Kyriakos C. Neanidis (Center for Economic Studies and ifo Institute (CESifo), 2010)
We analyze the effect of European Union (EU) membership on financial dollarization for the Central and Eastern European countries. Using a unique monthly dataset that spans about two decades, we find that both the accession process toward EU membership and EU entry have a direct impact on deposit and loan dollarization. EU membership reduces deposit dollarization while it increases loan dollarization. The negative effect on deposit dollarization captures the increased confidence of the private sector in the domestic currency as they consider the EU admission process to reflect their government's commitment in promoting policies of long-run currency stability. The positive impact on credit dollarization is the outcome of a greater convergence of exchange rates to the euro and the subsequent anticipation for a lower currency risk, which diminishes the cost of foreign currency borrowing.
Keywords: E44; F31; G11; G20; 330; financial dollarization; European Union membership; accession process; Währungssubstitution; Wechselkursrisiko; Erwartungstheorie; EU-Erweiterung; EU-Staaten (Osteuropa); Ostmitteleuropa